No Guarantee: Feminism’s Academic Affect and Political Fantasy - Wiegman, Robyn (Atlantis, 2016)
Both an assessment of the political present and a deliberation on feminist desires for a transformed future, this essay draws on nearly three decades of the author’s engagement with Women’s Studies and its academic institutionalization in order to identify both new and ongoing challenges to the intellectual and political life of the field.